2016
DOI: 10.5194/gmd-2016-184
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global 7-km mesh nonhydrostatic Model Intercomparison Project for improving TYphoon forecast (TYMIP-G7): Experimental design and preliminary results

Abstract: Abstract. Recent advances in high-performance computers facilitate operational numerical weather prediction by global hydrostatic atmospheric models with horizontal resolution ~ 10 km. Given further advances in such computers and the fact that the hydrostatic balance approximation becomes invalid for spatial scales

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…The microphysics included in the NHM and CPL is therefore important for TC simulations. Differences of the microphysics between models may therefore result in qualitative differences of the inner core structure of TCs (Nakano et al, ). Microphysics may also quantitatively affect the sensitivity of simulated TC intensities to air‐sea interfacial processes such as SSC and sea spray parameterization through differences in the estimates of latent heating.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The microphysics included in the NHM and CPL is therefore important for TC simulations. Differences of the microphysics between models may therefore result in qualitative differences of the inner core structure of TCs (Nakano et al, ). Microphysics may also quantitatively affect the sensitivity of simulated TC intensities to air‐sea interfacial processes such as SSC and sea spray parameterization through differences in the estimates of latent heating.…”
Section: Discussionmentioning
confidence: 99%
“…However, the horizontal resolution of the operational model of the global atmosphere has currently not reached 5 km. Nakano et al () have also demonstrated that a TC intensity forecast can even vary among different models with the same horizontal resolution of 7 km.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…We found that the predicted flood hydrographs of the 10 test events generally matched the actual flood hydrographs providing a long lead time (e.g., several days), with acceptable variation in the timing and volume of peak flows. This is a major improvement of existing prediction modeling approaches (e.g., physical, conceptual, and data-driven) that focus on rainfallrunoff mechanisms providing a short lead time (e.g., one-to sixhour) [36][37][38] . Figures 7-9 present the predicted flood hydrographs of the three test typhoon events (i.e., Typhoon Fitow, Typhoon Soulik, and Typhoon Dujuan, respectively) under three TD schemes implemented with the two FCC selection strategies.…”
Section: Resultsmentioning
confidence: 99%
“…A higher resolution model is needed to improve the representation of the structure of the TC's inner core, which results in accurate simulation of rapid intensification (Rogers et al 2013;Wang and Wang, 2014). Interestingly, a recent study shows that high-resolution global models reduce forecast error in TC intensity and tracking forecasts (Nakano et al 2017). The atmosphereocean interacting processes should also be incorporated in the numerical model to avoid overintensification (Wada et al 2014;Zarzycki 2016).…”
Section: Future Directionsmentioning
confidence: 99%